Growth Performance, Apparent Ileal Digestibility, and Nutrient Transporter Gene Expressions of Broilers Fed Seaweed-Supplemented Diets - Azizi, M. N.; Loh, T. C.; Foo, H. L.; Izuddin, W. I. (Faculty of Animal Science, IPB University, 2024)
Seaweed provides macro-, micro-nutrients, and biological bioactive components that may improve broiler production. The study aimed to evaluate the effects of various levels of brown seaweed (BS) and green seaweed (GS) on growth performance, carcass characteristics, apparent ileal digestibility (AID), and hepatic growth and nutrient transporter gene expressions. The study followed a completely randomized design (CRD) (twelve treatments, six replicates, and seven birds per replicate). The dietary treatments contained: basal diet [negative control (NC)], basal diet + vitamin E (100 mg/kg feed) [positive control (PC)], basal diet + 0.25%, 0.50%, 0.75%, 1.0%, and 1.25% BS and GS, respectively. The data were analyzed using the General Linear Model (GLM) of the statistical analysis system (SAS 9.4) by one-way ANOVA. Duncan’s Multiple Range Test was used to assess the significant differences between treatment groups at p<0.05. Various levels of BS and GS (p<0.05) improved body weight (BW), body weight gain (BWG), and feed intake (FI) at the starter phase. No significant effects were observed in the carcass characteristics. The AID of crude protein (CP), organic matter (OM), and dry matter (DM) during the starter phase were significantly improved. The hepatic growth hormone receptor (GHR) gene had increased expression in birds fed 0.50% and 0.75% of GS-contained diets. Similarly, birds fed 0.50% of BS and 0.25%, 0.50%, and 0.75% of GS had higher (p<0.05) expression of the hepatic Insulin-like growth factor-1 (IGF-1) gene. Furthermore, there were no significant effects on the intestinal nutrient transporters genes, including aminopeptidase (APN), glucose transporter (SGLT5), and oligopeptide transporter (PepT1) at the jejunum tissue. It was therefore concluded that different levels of BS and GS in the broiler chickens’ diet improved the starter period growth performance and nutrient digestibility.